In-Hospital Outcomes of Acute Kidney Injury After Pediatric Cardiac Surgery: A Meta-Analysis - Van den Eynde, Jef; Rotbi, Hajar; Gewillig, Marc; Kutty, Shelby; Allegaert, Karel; Mekahli, Djalila (Frontiers in Pediatrics, 2021)
Background: Cardiac surgery-associated acute kidney injury (CS-AKI) is associated with increased morbidity and mortality in both adults and children. This study aimed to investigate the in-hospital outcomes of CS-AKI in the pediatric population. Methods: PubMed/MEDLINE, Embase, Scopus, and reference lists of relevant articles were searched for studies published by August 2020. Random-effects meta-analysis was performed, comparing in-hospital outcomes between patients who developed CS-AKI and those who did not. Results: Fifty-eight publications between 2008 and 2020 consisting of 18,334 participants (AKI: 5,780; no AKI: 12,554) were included from studies. Higher rates of in-hospital mortality (odds ratio [OR] 7.22, 95% confidence interval [CI] 5.27-9.88), need for renal replacement therapy (RRT) (OR 18.8, 95% CI 11.7-30.5), and cardiac arrhythmias (OR 2.67, 95% 1.86-4.80) were observed in patients with CS-AKI. Furthermore, patients with AKI had longer ventilation times (mean difference [MD] 1.76 days, 95% CI 1.05-2.47), pediatric intensive care unit (PICU) length of stay (MD 3.31, 95% CI 2.52-4.10), and hospital length of stay (MD 5.00, 95% CI 3.34-6.67). Conclusions: CS-AKI in the pediatric population is associated with a higher risk of mortality, cardiac arrhythmias and need for RRT, as well as greater mechanical ventilation time, PICU and hospital length of stay. These results might help improve the clinical care protocols prior to cardiac surgery to minimize the disease burden of CS-AKI in children. Furthermore, etiology-specific approaches to AKI are warranted, as outcomes are likely impacted by the underlying cause.